Frequency-domain and stochastic model for an articulated wave power device - Cândido, J. (2009)
To have the first look into device performance, analytical and numerical tools must be used. Assuming that the wave power system hydrodynamics has a linear behaviour, diffraction and radiation coefficients can be computed. If the power take-off equipment may be, for the first approach, regarded as holding a linear behaviour then overall (i.e. hydrodynamic plus mechanical) device performance can be studied for regular waves. In this study a frequency-domain model describes the articulated system behaviour for regular waves. For this paper a stochastic model is found for an articulated wave power device, and probability density functions are defined for the relevant parameters that characterize the wave power system behaviour. For these parameters and for different sea states the probability density functions are found. The articulated system is characterized by these probability density functions. Also, average values for capture width are obtained for these sea state conditions.